2014
DOI: 10.1016/j.jphys.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence does not support the use of Kinesio Taping in clinical practice: a systematic review

Abstract: This review provides the most updated evidence on the effectiveness of the Kinesio Taping for musculoskeletal conditions. The current evidence does not support the use of this intervention in these clinical populations. PROSPERO registration: CRD42012003436.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(139 citation statements)
references
References 22 publications
7
120
1
11
Order By: Relevance
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared to previous studies, the findings of this review are in agreement with the previous systematic reviews that also found no effects of KT in stroke subjects 16 and other populations [11][12][13] . Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 .…”
Section: Discussionsupporting
confidence: 91%
“…Apparently, the growing use of KT is due mainly to massive marketing campaigns conducted by the media, ignoring the need for high-quality research, that is, scientific evidence with clinically relevant results 11 . Some authors of clinical trials with KT even recommended the use of the technique, even when their data have identified nothing significant 11 . Thus, professionals should carefully evaluate the costs and the effectiveness of this intervention when deciding for its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation/mobilization (Gross et al, 2015b) Electrotherapy (Kroeling et al, 2013) Physical modalities (Graham et al, 2013) Massage (Patel et al, 2012) Therapeutic exercise (Cheng et al, 2015b, Gross et al, 2015a Patient education Dry needling Kinesio taping (Parreira Pdo et al, 2014) Cognitive behavioral treatment (Monticone et al, 2015b) Current guidelines and evidence recommend the inclusion of active exercise, consisting of strengthening exercises, in the management of chronic neck pain (O'Riordan et al, 2014). …”
Section: Little To Moderate Effectmentioning
confidence: 99%
“…Embora alguns autores relatem melhora da dor e função através do uso da bandagem elástica [26][27][28] , uma série de revisões sistemáticas atuais tem demonstrado que a diminuição da dor pode estar relacionada a um efeito placebo [30][31][32] . No presente estudo, um indivíduo teve queixa álgica na região lombar no período em que permaneceu com a bandagem, sendo esta resolvida no momento da sua retirada.…”
Section: Discussionunclassified